Junction Site Analysis of Chimeric CYP21A1P/CYP21A2 Genes in 21-Hydroxylase Deficiency - Chen, Wuyan (Clin Chem, 2011)
BACKGROUND: Chimeric CYP21A1P/CYP21A2 genes, caused by homologous recombination between CYP21A2 (cytochrome P450, family 21, subfamily A, polypeptide 2) and its highly homologous pseudogene CYP21A1P (cytochrome P450, family 21, subfamily A, polypeptide 1 pseudogene), are common in patients with congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21-OHD). A comprehensive junction site analysis of chimeric CYP21A1P/CYP21A2 genes is needed for optimizing genetic analysis strategy and determining clinical relevance. METHODS: We conducted a comprehensive genetic analysis of chimeric CYP21A1P/CYP21A2 genes in a cohort of 202 unrelated 21-OHD patients. Targeted CYP21A2 mutation analysis was performed, and genotyping of chimeric CYP21A1P/CYP21A2 genes was cross-confirmed with Southern blot, RFLP, and multiplex ligation-dependent probe amplification analyses. Junction sites of chimera genes were determined by sequencing the long-PCR products amplified with primers CYP779f and Tena32F. An updated bioinformatics survey of Chi-like sequences was also performed. RESULTS: Of 100 probands with a chimeric allele, 96 had a chimera associated with the severe classic salt-wasting form of CAH, and the remaining 4 carried an uncommon attenuated chimera with junction sites upstream of In2G (c.293−13A/C>G), which is associated with a milder phenotype. In addition to 6 of 7 reported chimeras, we identified a novel classic chimera (CH-8) and a novel attenuated chimera (CH-9). Attenuated chimeras explained prior genotype–phenotype discrepancies in 3 of the patients. Sequencing the CYP779f/Tena32F amplicons accurately differentiated between classic and attenuated chimeras. The bioinformatics survey revealed enrichment of Chi-like sequences within or in the vicinity of intron 2. CONCLUSIONS: Junction site analysis can explain some genotype–phenotype discrepancies. Sequencing the well-established CYP779f/Tena32F amplicons is an unequivocal strategy for detecting attenuated chimeric CYP21A1P/CYP21A2 genes, which are clinically relevant.